Carbon Nanotube Modified Poly HEMA/CNC Composite Sorbent for Selective Recovery of Rare Earth Metal Ions - Nurul Jamilah; Asep Riswoko; Adam Badra Cahaya (BRIN Publishing (Penerbit BRIN), 2024)
Rare earth elements (REEs) from secondary resources need to be purified before being used as critical raw materials. A novel type of carbon nanotube (CNT)–based composite sorbent has been developed to adsorb REE metal ions from a low concentration of aqueous solution. The composite sorbents prepared from HEMA, CNC, and CNT were characterized by FTIR and their adsorption properties by ICP-OES. The results showed that the adsorption performance of sorbents depends on their constituting materials and the pH of the feeding solution. The presence of CNTs in the sorbents helps increase adsorption efficiency while increasing contact time. The highest adsorption efficiency (98%) was achieved at pH 4 with a contact time of 90 minutes. The prepared composite sorbents showed better adsorption selectivity for cerium (Ce3+) ions than neodymium (Nd3+) and lanthanum (La3+).